1987
DOI: 10.1007/bf01966479
|View full text |Cite
|
Sign up to set email alerts
|

The effect of etodolac on type II collagen-induced arthritis in mice

Abstract: Type II collagen-induced arthritis (CIA) and mice was used as a model to evaluate the effect of etodolac on the arthritic and immunological parameters of the experimental disease. In a preventative protocol, a significant reduction was observed in the number of joints progressing to ankylosis. At high doses (16 mg/kg/day) a significant delay in the onset of arthritis was also observed. No significant effect was seen on the progression of the disease when etodolac was administered in established CIA. No consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Indomethacin slightly reduced the development of periarticular damage, which was not significantly affected by etodolac. These present results support previous studies demonstrating the anti-arthritic efficacy of etodolac in animal models [3,5]. In rats with adjuvant arthritis [3], etodolac reduced the development of bone damage, while aspirin and naproxen did not.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Indomethacin slightly reduced the development of periarticular damage, which was not significantly affected by etodolac. These present results support previous studies demonstrating the anti-arthritic efficacy of etodolac in animal models [3,5]. In rats with adjuvant arthritis [3], etodolac reduced the development of bone damage, while aspirin and naproxen did not.…”
Section: Discussionsupporting
confidence: 94%
“…In rats with adjuvant arthritis [3], etodolac reduced the development of bone damage, while aspirin and naproxen did not. It has also been reported that etodolac significantly decreased the number of ankylosed joints in mice with type II collagen arthritis [5]. These joints had been reported to be insensitive to nonsteroidal anti-inflammatory drugs, such as aspirin, naproxen, and benoxaprofen…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been reported that etodolac can improve the function of osteoarthritic joints in canines (Johnston and Budsberg, 1997;Budsberg et al, 1999). Etodolac suppresses osteoarthritis induced experimentally in limbs of mice (Wooley et al, 1987). High doses of etodolac are more effective than lower doses (Inoue et al, 1993).…”
Section: Introductionmentioning
confidence: 98%